2021
DOI: 10.1186/s12886-021-02070-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulse waveforms in response to intraocular pressure elevation determined by laser speckle flowgraphy in healthy subjects

Abstract: Background The influences of intraocular pressure (IOP) elevations on the pulse waveform in the optic nerve head (ONH) were evaluated using laser speckle flowgraphy (LSFG) in normal subjects. Methods This prospective cross-sectional study was conducted at the Nagoya University Hospital. An ophthalmodynamometer was pressed on the sclera to increase the IOP by 20 mmHg or 30 mmHg for 1 min (experiment 1, 16 subjects) and by 30 mmHg for 10 min (experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The optimal parameter to use in analyses is not yet known, although it should be noted that results were very similar whether using BOM (analogous to the hemodynamic pulsatility index) or RI (analogous to the hemodynamic resistance index). It has been reported that elevating IOP using an ophthalmodynamometer decreased BOS and increased RI but did not alter RR, 58 although it should be noted that adjusting for average IOP did not alter the statistical significance of any of the main results in our study. The participants were under clinical management at the discretion of the patient's clinician, so animal models in which relevant variables can be directly controlled may aid our understanding of the contribution of vessel stiffness to the true natural history of the disease.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The optimal parameter to use in analyses is not yet known, although it should be noted that results were very similar whether using BOM (analogous to the hemodynamic pulsatility index) or RI (analogous to the hemodynamic resistance index). It has been reported that elevating IOP using an ophthalmodynamometer decreased BOS and increased RI but did not alter RR, 58 although it should be noted that adjusting for average IOP did not alter the statistical significance of any of the main results in our study. The participants were under clinical management at the discretion of the patient's clinician, so animal models in which relevant variables can be directly controlled may aid our understanding of the contribution of vessel stiffness to the true natural history of the disease.…”
Section: Discussioncontrasting
confidence: 67%
“…IOP can affect some LSFG measurements. 58 In multivariable models, higher average IOP significantly modulated predictions of the rate of functional change based on MBR Ave in both tissue and vessels in the “glaucoma suspect” eyes but not in the “glaucoma” eyes (likely because IOP was being managed clinically). However, adjusting for IOP did not significantly alter the relations between the rate of functional change and any of the LSFG parameters related to vascular resistance.…”
Section: Resultsmentioning
confidence: 97%
“…Hence, no direct comparisons to cohorts with elder and female patients are possible. However, in a healthy eye, retinal perfusion remains similar during the day and usually also within different days of measurement [12,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that IOP and MAP were associated with FAI-T in the overall group of patients and the female patients. Iwase et al demonstrated that FAI in the ONH significantly increased with increasing IOP in healthy subjects [51]. In addition, Yanagida et al showed that FAI in the overall ONH was negatively associated with MAP [40].…”
Section: Pulse Waveform In the Onh And Antioxidant Capacity In Glaucomamentioning
confidence: 99%